Integration of Sharia Economy, Green Economy, and Sustainable Development Goals - Dede Aji Mardani; Irwan Fauzy Ridwan; Imas Siti Masuroh (International Journal of Nusantara Islam, 2026)
This study analyzes the integration of sharia economics, green economy, and the Sustainable Development Goals (SDGs) in strengthening the sustainable development model in Indonesia. Using a qualitative approach through in-depth interviews, field observations, and document analysis, this study found that sharia principles such as justice, balance, and benefit are aligned with the green economy agenda that emphasizes resource efficiency and environmental protection. The findings indicate that the implementation of Sharia financial instruments, such as productive zakat, green waqf, and green sukuk, significantly strengthens the funding of sustainable development projects and increases community participation. The coherence between the values of maqasid al-shariah and the SDGs targets makes sharia economics an effective ethical platform in the transition to low-carbon development. This study concludes that Sharia-green integration is a strategic approach to achieving inclusive and resilient development, although challenges remain, including limited regulations, inadequate institutional capacity, and limited public understanding. Recommendations for further research include the use of mixed methods, expanding the study to the halal industry sector, and developing an integrative theoretical framework based on maqasid and SDGs indicators.